Investigation of comorbidities of COVID-19 patients with hepatosteatosis using latent class analysis - Pasin, Ozge; Cetin, Sirin; Kaya, Ahmet Turan (Frontiers in Public Health, 2022)
Introduction: Coronavirus Disease 2019 (COVID-19) disease first appeared in Wuhan, China in December 2019. Subsequently, the pandemic spread rapidly throughout the entire world. The number of people who died from COVID-19 is rising daily due to the growing number cases. This retrospective study aims to classify patients with hepatosteatosis(HS) who had COVID-19, depending on additional disease characteristics and to compare survival times and death rates. Material and Methods: The study included 433 individuals with COVID-19 and HS at Amasya University Sabuncuoglu Serefeddin Education and Research Hospital. Additional disease characteristics of patients with HS were analyzed using latent class analysis(LCA) and the patients were divided into two groups. Results: The study results indicate that the survival time of the first group, which was formed as a result of the LCA, was significantly lower than that of the second group (p=0.038).The rate of diabetes, coronary artery disease, chronic rhythm disorder, chronic obstructive pulmonary disease (COPD) and chronic kidney disease was significantly higher in group 1 than in group 2 (respectively p<0.001; p<0.001; p<0.001; p<0.001; p=0.015). Discussion: In patients with HS, the presence of diabetes, coronary artery disease, chronic rhythm problem, COPD, and chronic renal disorders contributes to an increase in death rates due to COVID-19.